Congenital erythropoietic porphyria or Günther's disease along with a rare mandibular adenomatoid odontogenic tumor - Kaushal Mahendra Shah; Amol Karagir; Shridevi Adaki (Wolters Kluwer Medknow Publications, 2016)
Congenital erythropoietic porphyria (CEP), or "Günther disease," is a rare variant of porphyria. It is an autosomal recessive disease caused by deficient uroporphyrinogen III synthase (URO-III-synthase), the fourth enzyme in the heme biosynthetic pathway. We report a case of a young female with the typical clinical presentations of cutaneous photosensitivity characterized by hyper- and hypo-pigmentations, blister formations and scarring of light-exposed skin, mutilation of the toe fingers, dark-purple urine and erythrodontia with pinkish fluorescence under a Wood's lamp. The diagnosis was confirmed by decreased activity of URO-III-synthase in red blood cells and a porphyrin profile compatible with CEP. Presence of adenomatoid odontogenic tumor associated with impacted mandibular right canine was also noted.